Library survival and the economics of social change [soundrecording] - Downs, Anthony; Downs, Anthony; American Library Association. Conference (91st). (Los Angeles, Calif.: CREDR Corp., 1973)
Discusses from the sociologist's and economist's viewpoints, the background factors of our present social change, characteristics and functions of our libraries, specific challenges for librarians due to social change, and the meaning of all these factors.
American Library Association, 91st annual conference. Media: man, material, machine
Keywords: Libraries and society -- Congresses; Library Science